Quantum rotor tunnelling in methyl ethyl ketone and acetophenone studied using field-cycling NMR techniques - Abu-Khumra, Sabah (2013)
In the solid state the rotation of a methyl group is hindered by a potential barrier and at low temperature the rotational motion is characterised by quantum tunnelling. The Pauli Exclusion Principle imposes constraints on the allowable eigenstates of the methyl rotor and leads to a combination of spatial and spin variables. The characteristics of these quantum tunnelling states, labelled A and E, are explored experimentally and methods are investigated for creating prescribed non-equilibrium states. We will investigate and explore the tunnelling polarization associated with the A and E tunnelling-magnetic levels by means of field-cycling NMR. Secondary rf irradiation is used to drive A-E and E-A transitions associated with NMR tunnelling sidebands. This polarization is then transferred to the 1H Zeeman system at a field-dependent level-crossing where the methyl tunnelling frequency equals one or two times the 1H Larmor frequency. The level-crossing contact is a necessary step since the tunnel temperature cannot be measured directly with a pulse. A new pulse sequence is described and the resulting spectra are analogous to the solid effect and dynamic nuclear polarization. Therefore we assign the phrase ‘dynamic tunnelling polarization’ to describe the experiments. Two samples are studied in depth, methyl ethyl ketone and acetophenone which have tunnel frequencies of 495 and 1435 kHz respectively. The experiments investigate the phenomena as a function of a variety of physical parameters in order to determine the fundamental physics.